2014
DOI: 10.1097/brs.0000000000000208
|View full text |Cite
|
Sign up to set email alerts
|

Extradural Nerve Anastomosis Technique for Bladder Reinnervation in Spinal Cord Injury

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…These findings indicate that nerve transfer can induce recovery of sensation of bladder fullness and possibly the ability to empty the bladder, and thus may be an appropriate surgical treatment for patients who sustain lower motor neuron lesion-induced bladder dysfunction. Cadaver studies by us 2,4,5 and others 11,20 confirmed that nerve transfer for bladder and urethra reinnervation is feasible and generalizable for reinnervation of the lower motor neuron-lesioned human pelvic viscera. This nerve transfer surgery is considered to be well within the technical range of practicing peripheral nerve reconstruction neurosurgeons or plastic surgeons.…”
Section: Discussionmentioning
confidence: 75%
“…These findings indicate that nerve transfer can induce recovery of sensation of bladder fullness and possibly the ability to empty the bladder, and thus may be an appropriate surgical treatment for patients who sustain lower motor neuron lesion-induced bladder dysfunction. Cadaver studies by us 2,4,5 and others 11,20 confirmed that nerve transfer for bladder and urethra reinnervation is feasible and generalizable for reinnervation of the lower motor neuron-lesioned human pelvic viscera. This nerve transfer surgery is considered to be well within the technical range of practicing peripheral nerve reconstruction neurosurgeons or plastic surgeons.…”
Section: Discussionmentioning
confidence: 75%
“…b) Ventral roots are removed from L5 or S1 above the injured level and connected below the injured level to the S2 or S3 ventral roots that innervate the bladder [133][134][135][136][137]. c) A peripheral nerve is resected and inserted into the ventral tract of the thoracic spinal cord (corticospinal tract) for 4-5 mm and the distal end of the nerve is connected to a neuromuscular junction in a lower limb muscle [138].…”
Section: Nerve Bridgingmentioning
confidence: 99%
“…Zheng et al 10 conducted a randomized controlled trial on the contralateral C7 nerve that proved the feasibility of nerve transplantation in the treatment of upper limb motor dysfunction after spastic paralysis. We have improved on this surgical method to a certain extent, as reported in our previous studies 11–14. On the basis of these studies, we considered the possibility of a surgical method to treat lower limb dysfunction caused by hemiplegia.…”
mentioning
confidence: 94%
“…We have improved on this surgical method to a certain extent, as reported in our previous studies. [11][12][13][14] On the basis of these studies, we considered the possibility of a surgical method to treat lower limb dysfunction caused by hemiplegia.…”
mentioning
confidence: 99%